2013
DOI: 10.3109/14397595.2013.860695
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of incidence and risk factors for serious adverse events in rheumatoid arthritis patients with etanercept or adalimumab in Korea and Japan

Abstract: The IR of SAE in Japan, especially infection, was higher than that of Korea, which was attributed to the difference of demographic and clinical characteristics of RA patients and treatment profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In contrast, in the spine, we found no evidence that MRI is better than radiographs in detecting change of structural damage. Despite the disappointing results with MRI, our results are in line with previous studies, showing that spinal radiographic progression can be detected even in early phases of the disease (4,27). A recent study has shown that low‐dose computerized tomography of the spine is more sensitive at detecting new syndesmophytes than conventional radiographs, which promises to further expand our ability to detect change in axial damage (28).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, in the spine, we found no evidence that MRI is better than radiographs in detecting change of structural damage. Despite the disappointing results with MRI, our results are in line with previous studies, showing that spinal radiographic progression can be detected even in early phases of the disease (4,27). A recent study has shown that low‐dose computerized tomography of the spine is more sensitive at detecting new syndesmophytes than conventional radiographs, which promises to further expand our ability to detect change in axial damage (28).…”
Section: Discussionsupporting
confidence: 92%
“…From 813 abstracts, we selected 309 publications from 36 registers. Sixteen published reviews allowed us to identify 7 other registries with no publication identified in databases (hand search) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective registry of Korean patients with RA (REtrospective study for Safety and Effectiveness of Anti-RA treatment with biologiCs, RESEARCh) was established to evaluate the safety and effectiveness of biologic DMARDs [ 13 ]. Patients who meet the 1987 American College of Rheumatology criteria for RA who had ever been given biologic DMARDs from December 2000 to June 2011 were identified from the medical records of Hanyang University Hospital for Rheumatic Diseases and enrolled in the RESEARCh database.…”
Section: Methodsmentioning
confidence: 99%